Computational simulations of unsteady flow field and spray impingement on a simplified automotive geometry. Issue 171 (December 2017) - Kabanovs, Anton; Garmory, Andrew; Passmore, Martin; Gaylard, Adrian
Abstract: Accurately predicting vehicle soiling is important for maintaining a clear view for the driver and on board camera and sensor systems. In this work we study the soiling process on a scale model of generic SUV body, which is a vehicle type particularly susceptible to base contamination. The Spalart-Allmaras formulation of the IDDES model is used to compute the continuous phase and the dispersed phase is computed using Lagrangian particle tracking, both concurrently with the flow-field, and also as a post-processing approach using time averaged statistical information of turbulence in a stochastic dispersion model. The results are compared against experimental data and the discrepancies discussed with regard to the predicted and measured flow field and base pressure distribution. Good agreement with experiment is shown for the contamination pattern using the fully unsteady method, but the more economic stochastic model does not recover some important details. This is attributed to the role of spatially correlated flow structures around the wheel in entraining particles into the wake that the stochastic model cannot accurately represent. This leads to the conclusion that base soiling is a function of unsteady modes, elimination of which may potentially reduce spray deposition.